Gut Microbiota of Obese, Type 2 Diabetic Individuals is Enriched in Faecalibacterium prausnitzii, Akkermansia muciniphila and Peptostreptococcus anaerobius after Weight Loss - Remely, Marlene; Hippe, Berit; Zanner, Julia; Aumueller, Eva; Brath, Helmuth; Haslberger, Alexander G (Endocrine, metabolic & immune disorders drug targets, 2016)
Beside the influence of nutritional habits and reduced physical activity, metabolic syndrome is associated with alterations in the structure of gut microbiota influencing the inflammatory immune responses. Gut microbiota and microbial metabolic activities are known to affect the lipid and glucose metabolism, satiety and chronic low-grade inflammation in the metabolic syndrome. The aim of the study was to identify genera or even species affecting host metabolism in obesity and type 2 diabetes beside the common used indicator: Firmicutes/ Bacteroidetes ratio. Differences in gut microbiota were investigated in three groups of subjects over a four month intervention period: type 2 diabetics under GLP1-Agonist therapy, obese individuals without established insulin resistance, both receiving nutritional counseling concerning weight reduction, and a lean control group. Collection of fecal samples was accomplished at two time points, before treatment, and after four months of treatment. For identification of bacteria at species-level we used 454 high-throughput sequencing and fragment length polymorphism analysis based on IS-pro (Intergenic-Spacer-profiling). Five bacterial species, two bacterial genera, total bacterial abundance, and the Firmicutes/Bacteroidetes ratio were determined. Type 2 diabetics showed a higher Firmicutes/Bacteroidetes ratio even with an increase to the second time point (p=0.07). The abundance of B. thetaiotaomicron remained unaffected, whereas B. vulgatus significantly increased in type 2 diabetics (p=0.07) over the study period. Either Alistipes spp. showed an increase in type 2 diabetics between the time points (p=0.06). The abundance of F. prausnitzii (p=0.03) and A. muciniphila (p=0.03) also increased in type 2 diabetics over study period. In addition, the concentration of P. anaerobius (p=0.03) was significantly higher in type 2 diabetics after intervention compared to lean and obese controls. Our results clearly show a difference in the gut bacterial composition in type 2 diabetics compared to lean controls or obesity. Therefore, the ratio of Fimicutes/Bacteroidetes might only be an indicator, but a detailed view at species level is even more important in regard to distinction of their functions.